Rural-urban disparities in basic sanitation access among households: a multivariable decomposition analysis of Ethiopian demographic and health survey 2019 - Keleb, Awoke; Daba, Chala; Endawkie, Abel; Asmare, Lakew; Bayou, Fekade Demeke; Abeje, Eyob Tilahun; Ayres, Aznamariam; Mohammed, Anissa; Kebede, Natnael; Abera, Kaleab Mesfin; Mekonen, Asnakew Molla; Gebeyehu, Endalkachew Mesfin; et al. (Frontiers in Public Health, 2024)
Introduction: Rural-urban disparities in basic sanitation access pose critical challenges to public health and human development. Understanding the determinants of this gap is vital for advancing the Sustainable Development Goals (SDGs) and improving environmental and public health through evidence-driven interventions.Objective: This study aims to analyze and understand the disparities in access to basic sanitation services between rural and urban households in Ethiopia.Method: This study used data from Ethiopian Demographic and Health Survey 2019 by analyzing 8,663 weighted households collected through stratified sampling techniques. The primary outcome was basic sanitation access, defined as access to flush or pour flush systems, septic tanks, pit latrines, or composting toilets. A multivariable decomposition analysis was conducted to identify factors contributing to rural-urban disparities with statistically significant variables determined at p<0.05 and 95% confidence interval.residence in pastoralist (10.10% widening) or agrarian regions (7.03% widening), and accessing water sources more than 30 minutes away (7.91% widening).Significant disparities exist in basic sanitation access between rural and urban households in Ethiopia. Factors such as age of household head, education level, family size, region of residence, and water source accessibility play crucial roles in these disparities. Addressing these factors is essential for improving sanitation access and achieving sustainable development goals.